Determinants of Tax Avoidance: Institutional Ownership as a Moderator - Aprivia, Carissa; Louw, Febriana (International Journal of Enterprise Modelling, 2025)
The purpose of this study is to examine the affects of accounting conservatism, independent commissioners, and inventory intensity on tax avoidance with institutional ownership as a moderator. This study was conducted quantitatively with research subjects consisting of companies on the Indonesia Stock Exchange listed during 2020-2024 in the industrial sector. The population studied in this research was composed of 67 companies using purposive sampling, resulting in 29 companies and a whole sample of 91 data after outliers. The data used was secondary data obtained from annual reports and company financial reports. The analysis techniques applied were multiple regression analysis and moderated regression analysis using IBM SPSS Statistics version 26. The outcome from this study reveal that accounting conservatism and independent commissioners have a negative impact on tax avoidance; inventory intensity doesn’t have impact on tax avoidance; institutional ownership is capable of weakening the impact of accounting conservatism on tax avoidance; and institutional ownership couldn’t moderate the impact of independent commissioners and inventory intensity on tax avoidance. Future research is expected to use sectors other than industry and add independent variables or use different moderating variables to provide broader insights.